Overexpression of the Wheat (Triticum aestivum L.) TaPEPKR2 Gene Enhances Heat and Dehydration Tolerance in Both Wheat and Arabidopsis - Zang, Xinshan; Geng, Xiaoli; He, Kexiang; Wang, Fei; Tian, Xuejun; Xin, Mingming; Yao, Yingyin; Hu, Zhaorong; Ni, Zhongfu; Sun, Qixin; Peng, Huiru (Frontiers in Plant Science, 2018)
Wheat (Triticum aestivum L.) yield and quality are adversely affected by heat, drought, or the combination of these two stresses in many regions of the world. A phosphoenolpyruvate carboxylase kinase-related kinase gene, TaPEPKR2, was identified from our previous heat stress-responsive transcriptome analysis of heat susceptible and tolerant wheat cultivars. Based on the wheat cultivar Chinese Spring genome sequence, TaPEPKR2 was mapped to chromosome 5B. Expression analysis revealed that TaPEPKR2 was induced by heat and polyethylene glycol treatment. To analyze the function of TaPEPKR2 in wheat, we transformed it into the wheat cultivar Liaochun10, and observed that the transgenic lines exhibited enhanced heat and dehydration stress tolerance. To examine whether TaPEPKR2 exhibits the same function in dicotyledonous plants, we transformed it into Arabidopsis, and found that its overexpression functionally enhanced tolerance to heat and dehydration stresses. Our results imply that TaPEPKR2 plays an important role in both heat and dehydration stress tolerance, and could be utilized as a candidate gene in transgenic breeding.